2019
DOI: 10.3390/ijerph16152731
|View full text |Cite
|
Sign up to set email alerts
|

Sociosexuality and Bright and Dark Personality: The Prediction of Behavior, Attitude, and Desire to Engage in Casual Sex

Abstract: Research about sociosexuality, understood as differences in people’s willingness to have sex without commitment in terms of its predictors, such as demographics, relationship status, or individual traits, such as personality, is still scarce. Although sociosexuality was initially considered unidimensional, a tridimensional structure—with behavior, attitudes, and desire as its components—is gaining momentum in the literature nowadays. The present study proposes to develop different predictive models for each di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Fifthly, a strong correlation was found between psychopathy and sadism. This also has been found in other studies using different instruments [12], supporting the idea that they may be the same thing, or different facets of a broader construct. Authors like Plouffe and colleagues [50] have highlighted that this overlap could be due to the way in which sadism is measured (i.e., using items that reflect psychopathic features) when we should focus instead on assessing the sadist's essence, like the enjoyment of cruelty or the tendency to subjugation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Fifthly, a strong correlation was found between psychopathy and sadism. This also has been found in other studies using different instruments [12], supporting the idea that they may be the same thing, or different facets of a broader construct. Authors like Plouffe and colleagues [50] have highlighted that this overlap could be due to the way in which sadism is measured (i.e., using items that reflect psychopathic features) when we should focus instead on assessing the sadist's essence, like the enjoyment of cruelty or the tendency to subjugation.…”
Section: Discussionsupporting
confidence: 84%
“…Personality, especially conceptualized as the "Big Five" personality traits (i.e., neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness), is one of the main personal variables related to successful adaptation at work [8,10] and to job performance [11]. However, at the same time that evidence in favor of the Big Five continues to grow, researchers are considering that it is necessary to extend the "bright" Big Five traits with other subclinical traits considered "dark": narcissism, Machiavellianism, and psychopathy [12][13][14][15]. Although all of them have common features like callousness, they are different traits [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that this dark side of personality was associated with poor quality relationships [26]. Regarding mating behavior, it has been found that people with higher scores in dark personality traits had a less restrictive sociosexuality, more sexual partners, and a greater orientation to short-term mating and casual sexual relationships [27,28]. Concerning the use of dating apps and dark personality, the main conclusions of the few available studies can be summarized in [7,15]: (1) the role of the Dark Core as a single dimension has not been evaluated, but instead, the relationships with the different dark personality traits have been explored;…”
Section: Introductionmentioning
confidence: 97%
“…In previous research, the traits of the tetrad have been associated with, to varying degrees, an earlier sexual debut ( Harris et al, 2007 ), a higher sex drive, impersonal sexual fantasies with multiple partners ( Baughman et al, 2014 ), an unrestricted sociosexual orientation (i.e., a willingness and desire to have sex in the absence of love and commitment; Foster et al, 2006 ; Holtzman and Strube, 2013 ; Jones and de Roos, 2017 ; Tsoukas and March, 2018 ; Fernández del Río et al, 2019 ), a higher likelihood of committing infidelity ( Jones and Weiser, 2014 ), and sexual risk-taking ( Dubas et al, 2017 ) that collectively signal heightened investment in short-term mating. Individuals expressing higher levels of the Dark Tetrad personality dimensions are also more likely to engage in aggression ( Paulhus et al, 2018 ), sexually coercion ( Koscielska et al, 2019 ), and criminal behavior (e.g., vandalism, illegal substance use, and assault; Edwards et al, 2017 ; Pfattheicher et al, 2019 ).…”
Section: The Dark Tetrad and Short-term Matingmentioning
confidence: 99%
“…There are several lines of evidence discussed in the preceding sections that support the argument that the Dark Tetrad personality characteristics may be relevant in understanding why certain men pay for sex. Like many male clients of prostitution, individuals higher on the Dark Tetrad traits tend to express a penchant for short-term and impersonal sex ( Holtzman and Strube, 2011 , 2013 ; Jonason et al, 2012 , 2015 ; Tsoukas and March, 2018 ; Fernández del Río et al, 2019 ), sexual risk-taking ( Dubas et al, 2017 ), a desire for stimulation and novelty ( Baumeister and Campbell, 1999 ; Carter et al, 2014 ), impulsivity ( Jonason and Tost, 2010 ; Jones and Paulhus, 2011 ), greater rape myth acceptance ( Jonason et al, 2017 ), lower emotional empathy ( Jonason and Krause, 2013 ; Jonason et al, 2013 ; Sest and March, 2017 ; Heym et al, 2019 ), as well as the perpetration of interpersonal aggression, violence, and criminal behavior ( Edwards et al, 2017 ; Paulhus et al, 2018 ; Pfattheicher et al, 2019 ). These findings also suggest that the Dark Tetrad may be especially prevalent among men expressing particular motives, including exciting and contemptuous sex with a variety of sex workers, commodified and business-like sex, and the desire to have power over and to control sex workers (see Figure 1 for predicted relations).…”
Section: Personality Prostitution and The Dark Tetradmentioning
confidence: 99%